The Effect of Green Accounting Implementation on Islamic University Social Responsibility: Peranan Green Accounting Terhadap Implementasi Islamic University Social Responsibility - Haryati, Tantina; Kirana, Nanda Wahyu Indah; Wilasittha, Acynthia Ayu; Putri, Sofie Yunida (Journal of Accounting Science, 2023)
Currently, various environmental issues are completely unavoidable, and even the implementation has begun to be applied in multiple sectors, including the world of education. This study aims to determine the implementation of IUSR-based Green Accounting at the Islamic University in Surabaya by using Sharia Enterprise Theory as the theoretical basis. The total population of this study is 1,311 students, consisting of 556 State Islamic University of Sunan Ampel Surabaya (UINSA) students, 530 Muhammadiyah University of Surabaya students, and 225 Nahdlatul Ulama University Surabaya (UNUSA) students. They were chosen using simple random sampling with a total sample according to the calculation of the Slovin formula. The hypothesis in this study is that Green Accounting, as measured by the indicators of Environmental Concern, Environmental Involvement, Environmental Reporting, and Environmental Audit have a significant effect on Islamic University Social Responsibility. The research variables were measured by indicators Al-Adl, Al-Ihsan, Maslaha, and Tafwid. The hypotheses were analyzed and tested using Partial Least Square (PLS) with SmartPLS 3.0 software, the results of which show that Green Accounting has a significant effect on Islamic University Social Responsibility. The implementation of green accounting in Islamic universities social responsibility should be implemented in every activity and activity that supports measurable environmental preservation through environmental performance at the university, which is measured by activities that support green accounting by participating in a green campus program so that the university's image becomes good in the eyes of society.